Hybrid Vigor: Securing Venture Capital by Spanning Categories in Nanotechnology - Wry, Tyler; Lounsbury, Michael; Jennings, P. Devereaux (Academy of Management Journal, 2014)
This study develops and tests a set of novel theoretical predictions about the conditions under which category spanning is rewarded by external audiences. To do this, we revisit the assumption that comprehensible organizational identities are associated with individual categories. Drawing on insights from cognitive psychology, we suggest that category spanning does not necessarily lead to confusion, but, rather, to interpretations that rely on a “header–modifier” structure where one category anchors cognition but is modified by features of the other. Audiences may have clear understandings about how categories fit together and cognate schema for evaluating firms that hybridize by spanning between them. An empirical examination of venture capital in the carbon nanotechnology industry supports our approach: start-ups were rewarded or punished for hybridization contingent on how they mixed “science” and “technology” in their patents, top management team, and collaborations. As such, we show that the category a firm starts in, how it hybridizes, and the degree to which this affects core versus peripheral identity markers may all affect how it is perceived.